2017
DOI: 10.1038/s41598-017-05579-4
|View full text |Cite
|
Sign up to set email alerts
|

Different Repeat Annual Influenza Vaccinations Improve the Antibody Response to Drifted Influenza Strains

Abstract: Seasonal influenza vaccine formulas change almost every year yet information about how this affects the antibody repertoire of vaccine recipients is inadequate. New vaccine virus strains are selected, replacing older strains to better match the currently circulating strains. But even while the vaccine is being manufactured the circulating strains can evolve. The ideal response to a seasonal vaccine would maintain antibodies toward existing strains that might continue to circulate, and to generate crossreactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
(60 reference statements)
3
16
0
Order By: Relevance
“…In the face of the vast antigenic diversity of IAV, not only in swine but also in humans and avian species, efforts have been focused on exploring mechanisms to potentiate immune responses to vaccine antigens to induce broader protection. Some approaches include testing different adjuvants to target specific pathways of the immune response (40)(41)(42), and others have examined various prime-boost strategies (43)(44)(45)(46)(47)(48)(49). One salient observation from our studies was a detectable back-boost in pigs that were vaccinated with one antigenic phenotype and challenged with an antigenically distinct virus.…”
Section: Discussionmentioning
confidence: 94%
“…In the face of the vast antigenic diversity of IAV, not only in swine but also in humans and avian species, efforts have been focused on exploring mechanisms to potentiate immune responses to vaccine antigens to induce broader protection. Some approaches include testing different adjuvants to target specific pathways of the immune response (40)(41)(42), and others have examined various prime-boost strategies (43)(44)(45)(46)(47)(48)(49). One salient observation from our studies was a detectable back-boost in pigs that were vaccinated with one antigenic phenotype and challenged with an antigenically distinct virus.…”
Section: Discussionmentioning
confidence: 94%
“…21 Possible solutions to this problem include vaccinating with strains that have drifted sufficiently from the previous vaccinating strain, and so are neutralised less effectively by circulating antibody. 22 Alternatively, in the absence of vaccine strain change, memory responses may be more effectively stimulated with adjuvants or a higher antigen dose.…”
Section: Discussionmentioning
confidence: 99%
“…We also quantified antibody titres against all other vaccine strains (Influenza A/California/7/2009 H1N1 pdm09; Influenza B/Brisbane/60/2008; and Influenza B/Phuket/3073/2013). Previous antigen exposure to other strains may affect the response rates in the general population ( 29,30 ; Table S1 ). Before the 2016/2017 influenza season, we observed that across all urban quarters a median of 21% (IQR 17-28.5%) had seroprotective antibody levels (defined as hemagglutination inhibition titres equal or more than 1:40 31 ) ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%